Mythological Narratives and Modern Reinterpretations in the Deconstruction of Narcissus Stories - -, Miranti; -, Mukodas; Balazs Huszka (Universitas Negeri Semarang, 2024)
A deconstructive analysis of the Narcissus story, particularly in the short story